2020
DOI: 10.1007/s00467-020-04522-6
|View full text |Cite
|
Sign up to set email alerts
|

Virus-specific T cells in pediatric renal transplantation

Abstract: After pediatric kidney transplantation, immunosuppressive therapy causes an increased risk of severe viral complications, especially from cytomegalovirus (CMV), BK polyomavirus (BKPyV) or Epstein-Barr virus (EBV), and less frequent from adenovirus (ADV). However, suitable predictive markers for the individual outcome of viral infections are missing and the therapeutic management remains a challenge to the success of pediatric kidney transplantation. Virus-specific T cells are known for controlling viral replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Also, high IPV could be associated with increased calcineurin inhibitor nephrotoxicity even in low tacrolimus trough level regimens [34,35]. Transplant‐associated infections like CMV or BKV infection could also have an association with high IPV (several intervals of over‐immunosuppression) and poor graft survival [36,37]. Another point is that patients included in this study underwent kidney transplantation between 2001 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Also, high IPV could be associated with increased calcineurin inhibitor nephrotoxicity even in low tacrolimus trough level regimens [34,35]. Transplant‐associated infections like CMV or BKV infection could also have an association with high IPV (several intervals of over‐immunosuppression) and poor graft survival [36,37]. Another point is that patients included in this study underwent kidney transplantation between 2001 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there is increasing evidence that Tvis mirror not only the virusspecific but also the general cellular immune defense. Thus, Tvis may serve as a marker to identify overimmunosuppression [36][37][38].…”
Section: Virus-specific T Cells As a Promising Biomarkermentioning
confidence: 99%
“…Also in children, it has been shown that the number of Tvis is associated with the risk of virus diseases [ 30 33 ]. Regarding the high incidence of post-transplant viral complications (especially in children), prophylaxis, diagnosis, and treatment of viral infections may be improved by the inclusion of Tvis-analysis in routine monitoring after kidney transplantation [ 36 , 37 ]. Besides, there is increasing evidence that Tvis mirror not only the virus-specific but also the general cellular immune defense.…”
Section: Innovative Non-cellular Biomarkersmentioning
confidence: 99%
“…Other markers, such as the "ImmuKnow" assay 22 or the measurement of Torque-Teno virus load, 9 have been evaluated retrospectively in this regard with variable results, but they have never been used in a prospective trial. Previously, Tvis measurements have been shown to improve management of post-transplant viral infections (for example, in CMV 10,23 or BK polyomavirus infection 11,13,14 ), but the value as a diagnostic marker of overimmunosuppression has not been hitherto assessed.…”
Section: Discussionmentioning
confidence: 99%
“…10 Accordingly, they may serve as an indicator of the intensity of immunosuppression as well as a prognostic marker for virus-induced diseases after transplantation. [10][11][12][13][14] The randomized IVIST trial has been designed to investigate the hypothesis that additional steering of immunosuppressive therapy by Tvis levels optimizes dosing of immunosuppressive therapy 15 (effect-related drug monitoring), resulting in a personalized treatment with improved clinical courses on the basis of fewer viral infections and possible changes in exposure to immunosuppressive drugs.…”
mentioning
confidence: 99%